Pemanfaatan Aplikasi Mobile Keluarga Berencana untuk Meningkatkan Kepatuhan Akseptor: Scoping Review: Utilization of Mobile Family Planning Applications to Improve Acceptor Compliance: A Scoping Review - Emiliana, Emiliana; Nova, Wahyuni Idvia (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Compliance of family planning (FP) acceptors in the use of contraceptive methods and accuracy of follow-up visits remain challenges in reproductive health services. Low compliance can reduce the effectiveness of FP programs and increase the risk of unplanned pregnancies. The use of digital technology, particularly mobile applications (mobile health/mHealth), has the potential to be an innovative solution to improve acceptor compliance through education and service reminders. This scoping review aims to evaluate the use of family planning mobile applications in improving acceptor compliance with contraceptive method use. This study used a scoping review design with the PRISMA-ScR framework. Data sources were original research articles obtained from the PubMed, ScienceDirect, Wiley, Research Rabbit, and Google Scholar databases published between 2020 and 2025. The study sample consisted of six articles that met the inclusion criteria after a selection process from 1,130 identified articles. Data collection was conducted using a data extraction sheet, while article quality assessment used the Joanna Briggs Institute (JBI) instrument The scoping review showed that family planning mobile applications increased acceptor compliance, particularly in terms of follow-up visit accuracy and continued contraceptive use.  Family planning mobile applications effectively improve contraceptive acceptor compliance, particularly in terms of follow-up visit accuracy and continued contraceptive use.